Perichondrial Progenitor Cells in Cartilage Tissue Engineering and Regenerative Medicine - Lin, Victor; Wang, Yu-Chieh; Watson, Deborah (Current Tissue Engineering (Discontinued), 2015)
Background: Restoration of human cartilage structures and function using materials highly similar to human native tissues remains to be a major challenge in bioengineering and orthopedics fields. The chondrogenic potential and quality of cellular components used in cartilage repair and tissue engineering have a profound impact on the function of cartilage constructs. Many types of somatic stem cells have been shown as potential sources to obtain the cellular components suitable for cartilage regeneration. Although mesenchymal stem cells derived from bone marrow and adipose tissues have long been known for and favored in chondrogenic applications, later discoveries indicate that perichondrial progenitor cells (PPCs) existing in cartilage perichondrium may provide greater capacity and advantages in cartilage repair and tissue engineering. The primary focus of this review article is to discuss human cartilage composition, clinical conditions requiring cartilage repair, the anatomical location and characteristics of PPCs, as well as their potential value in tissue engineering and regenerative medicine. Areas covered: A literature survey on the progenitors of chondrocytes using NCBI-PubMed and Google Scholar was performed in 2014 and 2015. The information and experimental results gathered from preceding studies were summarized and presented in this review article. Conclusion: Recent advances in stem cell biology and regenerative medicine provide hope for new strategies to treat cartilage lesions. PPCs have been considered a potential source for the cellular component suitable for cartilage repair and tissue engineering. Emerging evidence has suggested that these cells play critical roles in cartilage regeneration in vivo, and that they could be an ideal cellular material for cartilage reconstruction and tissue engineering due to their proliferative capacity and strong propensity for chondrogenic differentiation. We believe that further studies and characterization in human PPCs and their chondrogenic differentiated derivatives will provide important information that could assist the development of better regeneration and tissue engineering approaches to treat cartilage disease and injury.
Keywords: perichondrial progenitor cells